Study on the Anti-inflammatory mechanism of volatile components of hebei Aster tataricus before and after honey-fried based on gas chromatography-mass spectrometry and network pharmacology - Lv, Lijuan; Wang, Xiangpei; Wu, Hongmei; Zhong, Ke; Xu, Feng (Penerbit Universiti Kebangsaan Malaysia, 2022)
Aster tataricus (AT) and honey-fried Aster tataricus (HAT) have a significant effect on relieving cough and reducing sputum, both of which contain many volatile components. Studies have shown that the volatile components of AT and HAT may have an anti-inflammatory effect, but the mechanism is unclear. This study aimed to analyze the daodi herb of Hebei AT and HAT qualitatively and quantitatively using gas chromatography-mass spectrometry and systematically explored the similarities and differences of anti-inflammatory molecular mechanisms of volatile components Hebei AT and HAT by using network pharmacology. These results indicate that there are significant differences in volatile compositions and percentage contents between AT and HAT. Moreover, the anti-inflammatory mechanism of volatile components of Hebei AT and HAT have more prominent similarities and fewer differences. AT and HAT’s similar potential active components such as humulene,γ-muurolene, α-phellandrene, and acetic acid were nine. The similar key gene targets were forty-seven, such as CAT, GAPDH, HMOX1, and CTH. The potential active ingredients peculiar to HAT were furfural, β-elemene, methyleugenol, and unique targets of EIF6 and PKIA. It suggests that HAT had its characteristics in clinical anti-inflammatory. Their active anti-inflammatory components and percentage contents were different, and HAT was higher than that of AT. The anti-inflammatory effect of volatile components of HAT may be better than that of AT. These results provide a theoretical basis for the study of the anti-inflammatory molecular mechanism of AT and HAT.